Abenaki basketry - Pelletier, Gaby (Book collections on Project MUSE., 1982)
Splint basketry was an integral part of the economy and way of life of the St. Francis Abenaki at Odanak, but is now a pastime for the elderly. This report explores the reasons for its fading influence on Native culture.